Produção e nutrição mineral de milheto e de milho adubados com biofertilizante suíno em diferentes épocas no norte de Minas Gerais - Elwira Daphinn Siiva Moreira (2012)
The production of forage fertilized with swine biofertilizer in the semiarid north Minas Gerais can provide effects on productivity, development of culture and nutritional characteristics of plants and soil, favoring family farmers, due mainly to the economy of chemical fertilizers and sustainability of the agricultural systems, besides promoting the production of silage of better quality and still give a environmentally correct destination for pig manure. The objective of this research was to evaluate the yield and nutrition of millet and maize fertilized with doses of swine biofertilizer, at different times in the north of Minas Gerais. The experiments were conducted on an Oxisol simultaneously deployed during the period June to September 2011 and again conducted in October 2011 to February 2012. In both, it was used a randomized block design with four replications and six treatments: doses of swine biofertilizer to provide 0, 50, 100, 150 and 200 kg ha-1 P2O5, and an additional treatment with mineral fertilizer (571.4 kg ha-1 formulation 4-14-8). It was found that the morphological characteristics and the production of fresh and dry matter of millet and maize plants, except the morphological characteristics of corn plants were affected by treatments, with the highest yield obtained with mineral fertilizers and with higher doses of swine biofertilizer, showing the efficiency of fertilization of swine biofertilizer in the production of these forage. The swine biofertilizer was source of macronutrients and micronutrients for the crops.